35th Australian and New Zealand Society for Neuropathology (ANZSNP) Scientific Meeting - Meeting Abstracts, August 31st - September 1st, 2024 - The Australian; New Zealand Society for Neuropathology (ANZSNP) (Free Neuropathology, 2024)
The ANZSNP scientific meeting 2024 was held in the scenic city of Queenstown, New Zealand on 31 August and September 1. Dr Fouzia Ziad, President of the ANZSNP and Dr Laveniya Satgunaseelan, Secretary /Treasurer of the ANZSNP were the convenors of the meeting. The meeting was co-badged with the Australasian Winter Conference on Brain Research (AWCBR) 2024. There were 55 registrants from Australia, New Zealand, USA, Europe and Asia. The academic program covered a wide range of neuropathology topics ranging from neuro-trauma to neuro-oncology. The neuro-oncology sessions featured a series of lectures on updates in the classification and diagnosis of various CNS tumours delivered by keynote speaker Prof Arie Perry, UCSF. Dr Thomas Robertson presented an approach to frozen sections in surgical neuropathology. An interactive session on the RCPA Neuropathology Quality Assurance Program (QAP) was organised with the QAP convenor, Dr Barbara Koszyca. Prof David Capper delivered the plenary lecture on “DNA methylation profiling and its practical implications” during the combined session with AWCBR attendees. Combined sessions also featured presentations on non-neoplastic conditions such as neurotrauma and neurodegeneration, comprising of presentations from invited faculty including Prof Michael Buckland, Dr Helen Murray and Prof Glenda Halliday. Four scientific research papers and 3 interesting cases were selected for oral presentation by the scientific committee. The meeting concluded with a plenary lecture delivered by Prof Arie Perry on “Biomarkers in Neuro-oncology”. Two of the research paper presentations were eligible for the Bill Evans Memorial award for postgraduate students or trainees. The prize was awarded to Dr Monish Maharaj for his presentation “DNA Methylation Profiling to categorise meningioma recurrence risk: optimisation of resource allocation for patient selection”. The feedback from the participants suggested that the meeting was well organized and appreciated for its educational content.